Finance and Development, December 1985. (Finance and Development; Finance and Development ;, 1985)
This paper elaborates the introduction of surveillance that gave the IMF broader responsibilities with respect to oversight of its members' policies than existed under the par value system. The IMF's purview has been broadened under the new system but, by the same token, its members are no longer obliged to seek its concurrence in changes in exchange rates. The continuing volatility of exchange rates, and their prolonged divergence from levels that appear to be sustainable over time, have been matters of growing concern.